Kearifan Dialogis Nabi Atas Tradisi Kultural Arab: Sebuah Tinjauan Hadis - Syaikhudin, Syaikhudin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
There is a lots of local traditions arab wisely maintained and preserved by the Prophet. It’s like, the pilgrimage to Mecca, the rule of law marriages, deaths, versification, and many more. All of this can be found in many Hadith are scattered in the books of hadith. The Prophet is in order to reconcile Islam with the forces of the local Arab culture, it is done so that the local Arab culture is not lost. Thus, the face of Islam as a religion that rahmatan li al-’Alamin, a religion that has a high appreciation of the tradition will be seen.